Comparative study of local scour methods at bridge piers in the toribio river (2023)
Local scour is a morphological process originated by the presence of a foreign object or an obstacle within water flow alignment; therefore, bridge piers act as the cause of this phenomena, generating a significant bed level change in a river´s cross section. There are many methods and equations formulated in order to calculate or estimate local scour at a bridge pier thus resulting in a wide range of calculated values for local scour within a specific river. This research compares different local scour methods by calculating the scour depth at a bridge pier on the Toribio River, which is born in the Sierra Nevada mountain at the north of Colombia and drains westwards towards the Caribbean Sea. The construction of the railway bridge over the Toribio River in Colombia, makes it necessary to evaluate the bridge pier scour that the bed level will suffer, thereby guaranteeing a safe design for the bridge’s foundations. Seven different calculation methods for local scour are evaluated, analyzing various parameters such as: normal water depth, water flow, velocity, grain size and the pier´s geometry and size. The results for local scour obtained with each method are compared with measured scour results based on bathymetric data. Two bathymetric surveys provided information for initial and final bed levels at the cross section where the new bridge was built. The difference between initial bed level (December 2019) and final bed level (November 2020) indicated a measured local scour depth at both piers; this information served as a reference value for evaluating the seven different local scour equations. The local scour methods proposed by Laursen and Toch, Neill, Coleman and CSU, showed the results that best fitted with measured scour values, being the first two the most accurate ones for the study case of Toribio River.